Can Trust Be Streamed? The Influence of Digital Voices on Gen Z’s Repurchase Intention - Suziana, Suziana; Usman, Nurul Afifah; Verinita, Verinita (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
This study aims to examine the influence of online customer review, rating, and live streaming on trust and repurchase intention among Generation Z consumers in Padang, Indonesia. This paper contributes to digital marketing literature by exploring the mediating role of trust in e-commerce fashion purchases via Shopee. Using a quantitative approach, a purposive sampling method was applied to collect data from 200 Gen Z respondents who had purchased fashion products on Shopee within the last six months. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that online reviews and ratings significantly affect both trust and repurchase intention, while live streaming impacts trust but not directly repurchase intention. Trust also mediates the relationship between review and repurchase intention, and between live streaming and repurchase intention. These findings suggest that trust is a key driver of customer loyalty in digital commerce, especially among Gen Z.